Host immune response to SARS-COV-2 infection by TLR3, TLR4 and TLR7 gene expression through semi-quantitative retro-transcription PCR - Martinez Marignac, Veronica Lucrecia (2024)
Toll-like receptors (TLRs) involved in viral detection or overexpressed during infection, play also a main role in the subsequent development of fatal clinical manifestations in COVID-19 patients. We characterized by semiquantitative retro-transcription PCR the expression of TLR 3, 4, and 7 in nasopharyngeal total RNA samples from 150 and 152 individuals, positive and negative for COVID-19, respectively. All patients were grouped in accordance with the presence of respiratory symptoms, and results on rapid molecular diagnostic test (NeoKit S.A.) during 2021. Four groups were analyzed: a) COVID-19 RNA detected with severe symptomatology; b) COVID-19 RNA detected with low/mild symptomatology; c) COVID-19 RNA not detected with severe symptomatology; and d) COVID-19 RNA not detected with low/mild symptomatology. Other variables studied were age and sex. Our results show (while correcting the sample size bias of previous reports), a non-significant difference in the expression of TLR4/7 between COVID-19 positive and negative patients. Noteworthy, the expression of TLR3 was augmented in patients that resulted negative for COVID-19. When we compared the expression among the four groups, a significant positive correlation between severe symptomatology and TLR4 expression in patients positive and negative for COVID-19 was found. Furthermore, TLR4 gene expression was significantly amplified in those COVID-19 patients with severe symptomatology when compared with non-severe COVID-19 cases. Our data suggest that our innate TLRs immune system may respond differently to respiratory infections with similar symptomatology. We confirmed that mainly TLR3 and TLR4 could be involved in the response to respiratory pathogenesis and particularly TLR4 in COVID-19 infection with severe symptoms. In concordance with previous studies, we found that in inflammatory respiratory diseases it is important to focus on TLR3, and TLR4 gene expression to understand severe symptoms development. Research on these pathways may help to find modulators or antagonists to these genes, for future treatments